2006
DOI: 10.1016/j.jvs.2006.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and complications of temporary inferior vena cava filter placement

Abstract: Temporary IVC filters were effective for the prevention of fatal pulmonary embolism. However, our experience of a high incidence of complications related to temporary filters suggests that this device has limited indications and supports the need for innovative design of temporary filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 18 publications
0
55
1
1
Order By: Relevance
“…Contraindications to anticoagulation therapy were reported only in 9.1% of cases. 12 Similarly, thrombolysis was performed at a high rate (20.9%), which contrasts with the infrequent application of this technique in Western countries, as indicated in the RIETE (1.2%); this finding deviates from the recommendations of international and Japanese guidelines.…”
mentioning
confidence: 92%
“…Contraindications to anticoagulation therapy were reported only in 9.1% of cases. 12 Similarly, thrombolysis was performed at a high rate (20.9%), which contrasts with the infrequent application of this technique in Western countries, as indicated in the RIETE (1.2%); this finding deviates from the recommendations of international and Japanese guidelines.…”
mentioning
confidence: 92%
“…A temporary IVC filter is often used to avoid perioperative recurrence of PE, 13 but filter-related complications sometimes occur 14 and PE is an important one. 15 Thrombosis may occur at the insertion site or the site of the filter itself.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, temporary filters have been used to reduce the recurrence of PE in the acute phase, especially in Japan, but adverse effects may result (ie, infection, obstruction of filters, hematoma at insertion site). 17,18 Further precise indications for filters for the prevention of PE with high risks are required. Kucher et al reported that IVC filters were associated with a reduction in 90-day mortality in massive PE, 8 and several reports suggest that submassive PE because of RV dysfunction on echocardiography or CT identifies high-risk patients.…”
Section: Discussionmentioning
confidence: 99%